Analysis of 3-SPS/S Parallel Mechanism for Human Ankle Rehabilitation and Kinematic - Liu Xingfang; Miao Hongbin; Chen Jingyao; Liu Na (Jixie chuandong)
A 3-SPS/S parallel rehabilitation mechanism is proposed for the present situation of ankle rehabilitation institutions and the constitution of mechanism is introduced. The degree of freedom is calculated and the position inverse solution equation is established. Combined with numerical examples,the solution of the inverse equation is solved by MATLAB and the simulation results are verified by ADAMS. The simulation results show that the robot can meet the needs of ankle joint rehabilitation by changing the branching movement input.